PELESTARIAN NILAI TRADISIONAL MELALUI TARIAN SOYA-SOYA DI KOTA TIDORE KEPULAUAN - Alya Naurah Qurratu’Ain (STKIP Subang, 2026)
The Soya-Soya dance is one of the cultural heritages that has existed and developed in the community of Tidore City, North Maluku. This dance contains traditional values that are closely related to the spirit of struggle, courage, and togetherness of the Tidore community during the kingdom era. In this era of modernization, preserving these values is very important so that local cultural identity is not lost. This article was written to describe efforts to preserve customs through the Soya-Soya dance in Tidore. Thus, its social function, meaning, values, and inheritance practices can be passed on to the next generation.